STRATEGI PENINGKATAN KUALITAS PELAYANAN PUBLIK KOTA MAGELANG BERBASIS SMART CITY - yuliani, lisa; woyanti, nenik (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
Smart city Magelang City aims to provide services for the community effectively and efficiently. However, in its implementation, it experienced problems related to public services and community participation. The purpose of this study is to find out the solutions, innovations of the Magelang City government in public services, and E-community participation. This research applies a qualitative descriptive analysis approach. Primary data are obtained from competent experts from the Communication, Information and Statistics Service. Secondary data is obtained from DataGo and the Central Statistics Agency (BPS).The results of the study show the innovation of the Communication, Informatics, and Statistics Office of Magelang City to created Magelang Cerdas application that can facilitate the community in providing public services and free wifi services. The solution to the problem is to socialize to the community in smart city-based public services and make people technologically literate. The strategy recommendations are to strengthen cooperation between OPD, encourage people to participate in smart city-based public service policies, optimize the response of community aspirations and expand socialization of policies by means of social media, electronic media and direct socialization. Keywords: Smart City, Public, Technology, Government agencies